Pengaruh persistensi laba, free cash flow dan komponen-komponen akrual terhadap arus kas dari aktivitas operasi masa depan - Dita Saputri; Gustin Padwa Sari (Jurnal Akuntansi, Keuangan, dan Manajemen, 2020)
Purpose: This study aims to find empirical evidence of the influence of variables consisting of earnings persistence, free cash flow and accrual components of cash flows on operating activities in the future. Research methodology: The objects used in this study were manufacturing companies listed on the Indonesia Stock Exchange for 5 years (2013-2017). The study population consisted of 135 manufacturing companies listed on the Indonesia Stock Exchange. The sample selection technique used was purposive sampling, and the sample was 100 companies. Data were analyzed using the EVIEWS 9 program with the panel data regression analysis type. Results: The study finds that earnings persistence, free cash flow and accrual components of changes in account payable partially have a positive effect on cash flows from future operating activities, while the accrual component of changes in trade receivables and the accrual component of inventory changes partially do not have influence on cash flow from operating activities. Limitations: The limitation of this study was that manufacturing companies do not cover all company sectors listed on the Indonesia Stock Exchange. In addition to the data used in the study, only 5 years of annual financial reports were reported by each company to the Indonesia Stock Exchange Contribution: This research can be used by stakeholders, especially investors and creditors to assess the future prospects of a company through variables that have been tested which can affect cash flow from the future production activities by the company. Keywords: Cash flow from operating activities, Earnings persistence, Free cash flow, Accrual components